São as histórias que nos dizem mais: emoção, reflexão e ação na sala de aula - Rodrigo Aragao Soares (2007)
Upon arrival at Integrated Skills I, at Faculty of Letters UFMG, a University student of English lives a world surrounded by a multitude of memories, relations, beliefs, conflicts, ideologies, preferences as to his/her process of teaching-learning. The students previous experience and emotions influence his/her behavior in the classroom. In this domain, the students complex experience goes beyond what is argued by the overwhelming majority of second language acquisition theories. Being akin to western thinking, these theories limit, if not impede, the understanding of the historical and situated nature of the experience. Byputting into dialogue the Biology of Cognition with Narrative Inquiry and Ethnography, I put forth a systemic exercise that offers us powerful tools to understand this rich experience. With the use of many observation procedures, I indicate how the participants of this study reflect about their learning during a semesters course as they reveal milestones in their learning histories, identities, beliefs, feelings, conflicts and challenges. I claim that emotions, reflections and language learning histories modulate classroom interactions. To this end, I argue that as they tell their histories they become aware of the multiple aspects that influencetheir behavior as students. In this process their self-esteem improves. From then on, they can question certainties and alter emotions and actions that restrain their performance and development in the English language. Here they make their learning a conscious and effectiveprocess. We cannot deny the positive influence of reflection about ones language learning process, however, changing classroom behavior, if necessary, possible and wished for, may entail dealing with other emotions and aspects of the system that overcome those involved inreflective activity. The value of reflection resides in the possibility of a student assuming responsibility for the trajectory of his own history. Furthermore, by drawing concepts from Biology of Cognition, this work strengthens and offers contributions to prior studies that have made an effort to understand the intertwined complexity of the system that make upclassroom language learning experiences, such as: a) conflicts among beliefs, learning and teaching styles; b) the dynamic and unstable characteristic of students language learning emotions and identities; c) speaking English. I conclude by integrating the epistemology put forth in this study to effective and situated pedagogical practices.